Disappearing Palestine: Israel’s Experiments in Human Despair - Fernandez, Erwin S. (Kasarinlan: Philippine Journal of Third World Studies; Vol 29 No 1 (2014): The 2014 TWSC Writeshop)
Review of Disappearing Palestine: Israel’s Experiments in Human Despair by Jonathan Cook (London & New York: Zed Books)